Analisa Ketertarikan Masyarakat Terhadap Perbankan (Konvensional dan Syariah) - Titah Rahmawati (Prisani Cendekia, 2022)
This research to find out how the public's interest (interest) in banking (conventional banks vs. Islamic banks) and what factors are the determinants of society in choosing banking services. In Indonesia there are two kinds of banking operational systems, Conventional Banks and Islamic Banks. Bank is a business entity that collects funds from the public in the form of savings and distributes them back to the community in the form of loans (credit) in order to improve people's living standards. Meanwhile, Sharia Bank is a bank that carries out its business activities based on sharia principles or Islamic legal principles as regulated in the Fatwa of the Indonesian Ulema Council (MUI). All forms of banking operational activities, both conventional and sharia are under the supervision of the Financial Services Authority (OJK). The type of research used is descriptive to describe public interest in banking products (Conventional Banks vs. Islamic Banks), with data collection using a questionnaire as an instrument in the study, to see whether or not there are differences in public interest in banking (conventional banks vs. Islamic banks). by the same respondent. The results of this study are expected to be able to contribute to the banking sector, especially Islamic banking to carry out more socialization to the community, and is also expected to be a literature for all levels of society in need and as a motivation for other writers who want to conduct similar research with more creative and innovative methods